The managerial rents model: Theory and empirical analysis - Castanias, Richard P.; Helfat, Constance E. (Journal of Management, 2001)
Managerial resources, defined as the skills and abilities of managers, are important contributors to the entire bundle of firm resources that enable some firms to generate rents. Here we build on our original analysis (Castanias & Helfat, 1991) and present an expanded classification of managerial resources, elaborate on how this classification relates to the fundamental resource-based characteristics of value, scarcity, inimitability, and difficulty of substitution, and highlight the issue of appropriability of rents from managerial resources. We then move well beyond the original analysis to examine a large number of empirical implications of our model, including many contingency factors, and discuss recent empirical research. Finally, we suggest extensions of the model to include managerial cognition and social capital, and draw implications for resource-based theory more generally.